Strong Be-N Interaction Induced Complementary Chemical Tuning to Design a Dual-gated Single Molecule Junction - Sutradhar, Dipankar; Sarmah, Amrit; Hobza, Pavel; Chandra, Asit K (Chemistry (Weinheim an der Bergstrasse, Germany), 2023)
The interaction between pyridines and the π-hole of BeH2 leads to the formation of strong beryllium-bonded complexes. Theoretical investigations demonstrate that the Be-N bonding interaction can effectively regulate the electronic current through a molecular junction. The electronic conductance exhibits distinct switching behavior depending on the substituent groups at the para position of pyridine, highlighting the role of Be-N interaction as a potent chemical gate in the proposed device. The complexes exhibit short intermolecular distances ranging from 1.724 to 1.752 Å, emphasizing their strong binding. Detailed analysis of electronic rearrangements and geometric perturbations upon complex formation provides insights into the underlying reasons for the formation of such strong Be-N bonds, with bond strengths varying from -116.25 to -92.96 kJ/mol. Moreover, the influence of chemical substituents on the local electronic transmission of the beryllium-bonded complex offers valuable insights for the implementation of a secondary chemical gate in single-molecule devices. This study paves the way for the development of chemically gateable, functional single-molecule transistors, advancing the design and fabrication of multifunctional single-molecule devices in the nanoscale regime.
Keywords: single-molecule junction; π-hole; supramolecular chemistry; Beryllium bond; molecular electronics